2021
DOI: 10.1121/10.0003369
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual sensitivity to vowel quality and vowel length in the first year of life

Abstract: The perceptual attunement to native vowel categories has been reported to occur at 6 months of age. However, some languages contrast vowels both in quality and in length, and whether and how the acquisition of spectral and duration-cued contrasts differs is uncertain. This study traced the development of infants' sensitivity to native (Czech) vowel-length and vowel-quality contrasts. The results suggest that in a vowel-length language, infants learn to categorize vowels in terms of length earlier and/or more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…However, input analyses reveal that these contrasts are differentiated in natural speech to Japanese infants (Bion et al, 2013). These findings contrast with reports of discrimination of similar fricative and duration‐based contrasts in non‐Asian populations using similar paradigms (e.g., Larraza et al, 2020; Paillereau et al, 2021). For example, Czech infants discriminated native duration‐based distinctions early in life (Paillereau et al, 2021), arguing against these contrasts being a less salient source of acoustic contrast for infants universally.…”
Section: Representation Of Geographical Regionscontrasting
confidence: 99%
“…However, input analyses reveal that these contrasts are differentiated in natural speech to Japanese infants (Bion et al, 2013). These findings contrast with reports of discrimination of similar fricative and duration‐based contrasts in non‐Asian populations using similar paradigms (e.g., Larraza et al, 2020; Paillereau et al, 2021). For example, Czech infants discriminated native duration‐based distinctions early in life (Paillereau et al, 2021), arguing against these contrasts being a less salient source of acoustic contrast for infants universally.…”
Section: Representation Of Geographical Regionscontrasting
confidence: 99%
“…This finding is in line with the literature demonstrating that in newborns the most prominent auditory ERP is a positive peak slightly after 200 ms, which with age develops into a negative N1 peak as the prominent auditory ERP response, maturing into the P1-N1-P2 complex (Pictor & Taylor 2007, Wunderlich et al 2006 days, that is, 40 weeks and 1 day. The presence of an MMR for the durational contrast (and the failure to detect it for the spectral contrast) aligns with prior studies documenting more a robust perceptual sensitivity to vowel duration of vowel spectrum in Czech-learning infants (Chládková et al 2021, Paillereau et al 2021.…”
Section: Discussionsupporting
confidence: 87%
“…This prediction is based on the cue-specific properties of prenatal input, where durational cues are preserved in utero in an unchanged form, while spectral cues are modulated as they pass through tissues and amniotic water to the fetal ear (Richards et al 1992, Granier-Deferre et al 2011. Moreover, developmental studies with Czech-learning infants suggest more robust discrimination of vowel length compared to vowel quality across the first year of life, as well as exaggeration of durationally cued vowel contrasts in the infants' (prenatal) input (Chládková et al 2019. Paillereau et al 2021, Svoboda et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, native-language attunement to vowel-length contrasts might start sooner after birth than attunement to vowel-identity contrasts and the attentional demands associated with vowel-length discrimination may already be highest within the first two months of life, causing the vowel-length MMR amplitude to decrease linearly from 2 months on. Supporting this hypothesis, a recent behavioural study in Czech, a language in which vowel-length is also phonemic, found infants to be sensitive to vowel-length contrasts earlier than to vowel-identity contrasts ( Paillereau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%